A simple method for indexing Phytophthora and nematode infections in black pepper (Piper nigrum L.) - Y R SARMA, JOSE ABRAHAM, M ANANDARAJ, K V RAMANA (Journal of Spices and Aromatic Crops, 1996)
A simple method for indexing Phytophthora foot rot disease of black pepper (Piper nigrum) caused by the fungns P. capsici and the nematodes Radopholus similis and Meloidogyne incognita was derived. The index is based on foliar yellowing and defoliation which are the predominant aerial symptoms of the disease.